Peningkatan Kompetensi Guru IPA Melalui Pelatihan dan Pendampingan Pembuatan Perangkat dan Media Pembelajaran Berbasis Pendekatan Saintifik - Nurhayati Nurhayati; Dwi Fajar Saputri; Fety Novianty; Wahyudi Wahyudi (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2020)
This Community Partnership Program (PKM) aims to increase knowledge and train teachers in creating and applying learning tools based on scientific approaches that contain the character and creating and applying contextual and innovative media/teaching aids in learning. The method of implementing PKM activities consists of socialization, seminars, training, mentoring, and implementation. Participants in PKM activities are science teachers at SMP and equivalent who are members of the MGMP IPA for SMP Kota Singkawang. The results of the activity show that the teachers are enthusiastic about participating in the series of activities carried out; the teachers are motivated to make science learning media and apply them in classroom learning. Teachers are motivated to create and apply learning models based on scientific approaches with character learning in the classroom.